2012
DOI: 10.1073/pnas.1117704109
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional IR spectroscopy and segmental 13 C labeling reveals the domain structure of human γD-crystallin amyloid fibrils

Abstract: The structural eye lens protein γD-crystallin is a major component of cataracts, but its conformation when aggregated is unknown. Using expressed protein ligation, we uniformly 13 C labeled one of the two Greek key domains so that they are individually resolved in two-dimensional (2D) IR spectra for structural and kinetic analysis. Upon acid-induced amyloid fibril formation, the 2D IR spectra reveal that the C-terminal domain forms amyloid β-sheets, whereas the N-terminal domain becomes extremely disordered bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
308
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(329 citation statements)
references
References 36 publications
(88 reference statements)
19
308
2
Order By: Relevance
“…This spectrum is nearly identical to that of the unlabeled peptide, except that the amide features are downshifted uniformly by 44 cm −1 . Such a frequency shift is consistent with the change in effective mass upon 13 C substitution of the amide carbon and has been observed in other fully labeled peptide samples (25). The similarity between the spectra indicates that uniform 13 C labeling does not disrupt the structure or coupling of the peptides.…”
Section: Resultssupporting
confidence: 69%
“…This spectrum is nearly identical to that of the unlabeled peptide, except that the amide features are downshifted uniformly by 44 cm −1 . Such a frequency shift is consistent with the change in effective mass upon 13 C substitution of the amide carbon and has been observed in other fully labeled peptide samples (25). The similarity between the spectra indicates that uniform 13 C labeling does not disrupt the structure or coupling of the peptides.…”
Section: Resultssupporting
confidence: 69%
“…The new intense and sharp peak at ϳ1620 cm Ϫ1 indicates formation of amyloid ␤-sheets. The line-width and anharmonic shift of this feature are also consistent with amyloid fiber formation and comparable to what observed in previously studied amyloid fibrils (45)(46)(47)(48). Notably, a similar enrichment in ␤-sheet structure was observed in MPO-2:1-H 2 O 2 -apoA-I incubated under the same conditions (Fig.…”
supporting
confidence: 73%
“…The only difference is the vastly disparate timescales probed by the two methods -picoseconds versus milliseconds -, which refers to the "direct time resolution" inherent to both techniques. In the context of protein dynamics, 2D IR spectroscopy has been applied to investigate the structure of membrane peptides [21,22], fibril formation [23,24], the structural flexibility of enzyme active sites [25], ligand migration in heme proteins [26], ligand binding [27,28], and the dynamics of the protein hydration shell [29,30], to list just a few examples. Recent reviews can be found in Refs.…”
Section: Advancing the Sensitivitymentioning
confidence: 99%
“…For most cases, the -CO groups of the peptide backbone have been considered, either as single (-13 C 16 O) or as double (-13 C 18 O) substitution, where the latter is preferred since it completely separates the corresponding vibrational mode from the main amide I band. This approach has been used extensively to study structure and dynamics of small peptides [5, 7-9, 21, 22, 24, 34, 40-43], but unfortunately, it is essentially no longer feasible even for small proteins (elegant exceptions to that statement exist [23]). First, the synthesis becomes extremely tedious once the size of the protein exceeds that which can be handled on a peptide synthesizer ( > ∼ 50 amino acids), so the protein has to be expressed in E. coli.…”
Section: Advancing the Selectivitymentioning
confidence: 99%